1993
DOI: 10.1083/jcb.121.6.1311
|View full text |Cite
|
Sign up to set email alerts
|

Proton pumps populate the contractile vacuoles of Dictyostelium amoebae.

Abstract: Abstract. Amoebae of the eukaryotic microorganism Dictyostelium discoideum were found to contain an interconnected array of tubules and cisternae whose membranes were studded with 15-nm-diameter "pegs" Comparison of the ultrastructure and freeze-fracture behavior of these pegs with similar structures found in other cells and tissues indicated that they were the head domains of vacuolar-type proton pumps. Supporting this identification, the pegs were observed to decorate and clump when broken amoebae were expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
213
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(227 citation statements)
references
References 71 publications
13
213
1
Order By: Relevance
“…This suggested that these circular bodies surrounded by GFP-VwkA might be contractile vacuoles, dynamic organelles involved in osmoregulation (Gerisch et al, 2002). To explore this localization further, live GFP-VwkAexpressing cells were stained with FM2-10, a lipophylic styryl fluorescent dye that preferentially labels contractile vacuoles in living Dictyostelium cells (Heuser et al, 1993;Gerisch et al, 2002). As shown in the Figure 10B, one of the circular shaped bodies is stained with FM2-10 dye, indicating that VwkA is localized to contractile vacuole in the cells ( Figure 10B, top arrowhead).…”
Section: Intracellular Localization Of Gfp-vwkamentioning
confidence: 99%
“…This suggested that these circular bodies surrounded by GFP-VwkA might be contractile vacuoles, dynamic organelles involved in osmoregulation (Gerisch et al, 2002). To explore this localization further, live GFP-VwkAexpressing cells were stained with FM2-10, a lipophylic styryl fluorescent dye that preferentially labels contractile vacuoles in living Dictyostelium cells (Heuser et al, 1993;Gerisch et al, 2002). As shown in the Figure 10B, one of the circular shaped bodies is stained with FM2-10 dye, indicating that VwkA is localized to contractile vacuole in the cells ( Figure 10B, top arrowhead).…”
Section: Intracellular Localization Of Gfp-vwkamentioning
confidence: 99%
“…Well characterized acidosomes also have a tubulo-vesicular morphology in vitro ( Fig. 4; also see [8,9]) and in vivo [9,12,21], further supporting their putative function as an early endosomal compartment. Also note the smaller vesicles accumulated inside acidosomes (Fig.…”
Section: Resultsmentioning
confidence: 70%
“…It has been recently suggested that the tubulo-vesicular structure of the acidosome [22] in Dictyostelium is the contractile vacuole [12]. For the following reasons, we believe that contractile vacuoles and acidosomes are in fact two distinct organelles.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The giant vacuoles may be part of the CV since they apparently occurred in response to the changing osmolarity of the nutrient medium. Since excretion of the vacuolar contents presumably would occur through the CV complex, the giant vacuoles may be composite structures related to both endosomes and the CV, which are evidently different organelles (Gabriel et al, 1999) but share some common molecules (e.g., the vacuolar-H + -ATPase [Heuser et al, 1993;Nolta et al, 1993] and a Rab4-like GTPase [Bush et al, 1994]). These two organelle systems may be connected under certain osmotic conditions (Padh, 1995;Padh et al, 1991a,b;Steck et al, 1997).…”
Section: Discussionmentioning
confidence: 99%